O conceito de Amor em Ibn Sīnā Uma leitura a partir da Risāla ̍fi ’Al- ‘išq - Russo, Carolina Moreira [UNIFESP] (2017)
This research mainly aims to develop a study on the concepts that permeate the work Risāla ̍fi 'Al-' išq (Epistle about love) by the Persian philosopher Ibn Sina, accentuating the notion of Love. In addition to the research about Love, we present an introductory study on Islam and the study of falsafa, as our Western society is not very familiar with such themes. We have used the translation, reading, and exegesis of the abovementioned epistle as a method, which still has no translation into Portuguese, as well as the bibliography referring to Islam and falsafa. As a product of this research, we describe Love, according to Ibn Sīnā as a fitra, that is, a natural force and willingness, which is within all beings. Love is a tendency in the direction of the good of each thing, the force that moves things to meet its principle of perfection, which leads to the Supreme Good.